Quercetin Inhibits LPS-Induced Inflammation and ox-LDL-Induced Lipid Deposition - Xue, Feng; Nie, Xiaobo; Shi, Jianping; Liu, Qingxue; Wang, Ziwei; Li, Xiting; Zhou, Jinqiu; Su, Jia; Xue, Mingming; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Pharmacology, 2017)
Aberrant activation of inflammation and excess accumulation of lipids play crucial role in the occurrence and progression of atherosclerosis (AS). Quercetin (QCT) has been tested effectively to cure AS. It is widely distributed in plant foods and has been proved to have potential antioxidative and anticancer activities. However, the underlying molecular mechanisms of OCT in AS are not completely understood. In the present study, we stimulated murine RAW264.7 cells with lipopolysaccharide (LPS) or oxidized low-density lipoproteins (ox-LDL) to mimic the development of AS. The data show that QCT treatment leads to an obvious decrease of multiple inflammatory cytokines in transcript level, including interleukin (IL)-1α, IL-1β, IL-2, IL-10, macrophage chemoattractant protein-1 (MCP-1) and cyclooxygenase-2 (COX-2) induced by LPS. Moreover, expressions of other factors that contribute to the AS development, such as matrix metalloproteinase-1 (MMP-1) and suppressor of cytokine signaling 3 (SOCS3) induced by LPS are also downregulated by QCT. Furthermore, we found that QCT suppressed LPS-induced the phosphorylation of STAT3. Meanwhile, QCT could ameliorate lipid deposition and overproduction of reactive oxygen species (ROS) induced by ox-LDL, and block the expression of lectin-like oxidized LDL receptor-1 (LOX-1) in cultured macrophages. Taken together, our data reveal that QCT has obvious anti-inflammatory and antioxidant virtues and could be a therapeutic agent for the prevention and treatment of AS.